2021
DOI: 10.7759/cureus.15430
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Mass: Include Tuberculosis in the Differential Diagnosis

Abstract: Although abdominal tuberculosis (TB) is quite prevalent in endemic regions, involvement of the pancreas is considerably rare. We describe a case of pancreatic TB presenting as a pancreatic mass in a patient with abdominal pain and jaundice. Due to the similar presentation, it can easily be misinterpreted as a pancreatic neoplasm. Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) can help confirm the diagnosis in such cases by providing histopathological evidence of Mycobacterium tuberculosis infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Under these conditions, the particularities of our case consist, on the one hand, in the appearance of pancreatic tuberculosis in an immunocompetent patient, and on the other hand, in the detection of AFB in the intracystic fluid. Sohni et al reported a similar case, of pancreatic tuberculosis in an immunocompetent patient by detecting AFB in tissue samples obtained by fine-needle aspiration (FNA) and growth in culture of Mycobacterium tuberculosis [13]. Abbaszadeh et al presented another case of pancreatic tuberculosis in a 23-year-old woman without significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the particularities of our case consist, on the one hand, in the appearance of pancreatic tuberculosis in an immunocompetent patient, and on the other hand, in the detection of AFB in the intracystic fluid. Sohni et al reported a similar case, of pancreatic tuberculosis in an immunocompetent patient by detecting AFB in tissue samples obtained by fine-needle aspiration (FNA) and growth in culture of Mycobacterium tuberculosis [13]. Abbaszadeh et al presented another case of pancreatic tuberculosis in a 23-year-old woman without significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis has remained a major cause of morbidity and mortality in developing countries. Pancreatic tuberculosis is very rare and, in most cases, has been reported in immunosuppressed patients or in the context of disseminated disease [13]. The low probability of Mycobacterium tuberculosis localization at the pancreatic level could be explained by the retroperitoneal location of the pancreas and the antimicrobial properties of its enzymes, such as lipase and deoxyribonucleases extracts [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical manifestations, abdominal pain was the most common symptom in patients, followed by weight loss, low fever, jaundice, or acute pancreatitis. [6,7,[17][18][19][20][21][22][23][24][25][26] We retrospectively analyzed the cases of pancreatic tuberculosis published in the past 2 years and found that except one case without abdominal pain, the other cases all showed abdominal pain. It is obviously different from low back pain caused by pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of radiology examination, it is common for pancreatic tuberculosis to invade PV or peripheral blood vessels. [10,17] Rana et al [10] reported that PV, SMV, and hepatic artery were involved in 5 of 16 patients (31%). Therefore, the possibility of pancreatic tuberculosis cannot be ruled out simply by involving blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Duodenal TB may be associated with the involvement of other parts of the gastrointestinal tract in up to 50% of cases [ 9 ]. On the other hand, pancreatic TB can present as an abscess, mass, acute or chronic pancreatitis [ 2 , 3 ]. The head region is the most common site of pancreatic TB [ 14 ].…”
Section: Discussionmentioning
confidence: 99%